2001
DOI: 10.1002/ijc.10101
|View full text |Cite
|
Sign up to set email alerts
|

Family history and the risk of stomach cancer death in Japan: Differences by age and gender

Abstract: Familial aggregation of stomach cancer has long been observed. The effect on disease risk of family history and its magnitude according to the type of affected relatives, however, is not well known. We conducted a prospective analysis using the JACC study (Japan Collaborative Cohort Study For Evaluation of Cancer Risk, sponsored by Monbusho) data. During the follow-up period, 662 stomach cancer deaths were documented. A positive history of stomach cancer in one or more first-degree relatives was associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 30 publications
7
38
0
Order By: Relevance
“…This did not seem to be caused by a confounding of H. pylori infection. Some previous studies found stronger impact of family history on the disease risk in women than in men, which may partly be consistent with the present finding (Nagase et al, 1996;Yatsuya et al, 2002). Family history of stomach cancer was associated with a significantly increased risk of the disease (OR 4.5, 95% CI 1.3 -15.2) in women, whereas it was related to a nonsignificant increased risk in men (OR 1.2, 95% CI 0.6 -2.5) in a hospitalbased case -control study in Japan (Nagase et al, 1996).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This did not seem to be caused by a confounding of H. pylori infection. Some previous studies found stronger impact of family history on the disease risk in women than in men, which may partly be consistent with the present finding (Nagase et al, 1996;Yatsuya et al, 2002). Family history of stomach cancer was associated with a significantly increased risk of the disease (OR 4.5, 95% CI 1.3 -15.2) in women, whereas it was related to a nonsignificant increased risk in men (OR 1.2, 95% CI 0.6 -2.5) in a hospitalbased case -control study in Japan (Nagase et al, 1996).…”
Section: Discussionsupporting
confidence: 93%
“…Familial aggregation of stomach cancer has long been noted (Macklin, 1960;Toyoshima et al, 1997;Yatsuya et al, 2002;Kondo et al, 2003). Certain evidence, however, suggests that both genetic and environmental factors are responsible for familial clustering (Palli et al, 2001).…”
mentioning
confidence: 99%
“…Moreover, having a multiple family history of GC is a stronger risk factor for GC compared with no or a single family history of GC (ORs 5.7 and 1.7 in subjects with a multiple and a single family history of GC respectively) [5,6]. Our results may be consistent with those of previous studies indicting that GC risk was high in subjects with a multiple family history of GC, and among them the risk was especially high when both parents were affected [5,6]. Thus, a detailed family history assessment of cancer, including the number of affected first-degree relatives, is needed before genetic risk assessment [24].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that having a first-degree relative with GC is a consistent risk factor for GC [2][3][4], especially when two or more relatives are affected [5,6]. Familial aggregation of GC may be caused by shared environmental factors as well as common genetic backgrounds [7].…”
Section: Introductionmentioning
confidence: 99%
“…The relative risk (RR) and its 95% confidence interval (CI) were calculated based on the regression coefficient and its standard error (Cox, 1972), for an indicator term corresponding to the level of an independent variable. For multivariate analysis, several factors were listed as potential confounders according to epidemiological studies (Boeing, 1991;Hoshiyama and Sasaba, 1992;World Cancer Research Fund, 1997;Hoshiyama et al, 2002;Yatsuya et al, 2002). Trends of association were assessed by the regression model assigning scores (0 -4) to the levels of the independent variables.…”
Section: Data Processingmentioning
confidence: 99%